2021
DOI: 10.1021/acs.est.1c03106
|View full text |Cite
|
Sign up to set email alerts
|

Selective Leaching of Rare Earth Elements from Ion-Adsorption Rare Earth Tailings: A Synergy between CeO2 Reduction and Fe/Mn Stabilization

Abstract: The increasing demand for rare earth elements (REEs) motivates the development of novel strategies for cost-effective REE recovery from secondary sources, especially rare earth tailings. The biggest challenges in recovering REEs from ion-adsorption rare earth tailings are incomplete extraction of cerium (Ce) and the coleaching of iron (Fe) and manganese (Mn). Here, a synergistic process between reduction and stabilization was proposed by innovatively using elemental sulfur (S) as reductant for converting insol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The results obtained from in situ XPS spectra agreed with the XRD patterns of the solid residues obtained from the magnetic separation after residue sulfation (Figure C), in which magnetite (FeFe 2 O 4 ) and jacobsite (MnFe 2 O 4 ) were indexed. Previous research also reported the shorter bond lengths of Fe–O (2.05 Å) and Mn–O (2.01 Å) in the octahedral sites of FeFe 2 O 4 and MnFe 2 O 4 , respectively, than Ce–O (2.18 Å) of CeFe 2 O 4 after the geometry optimization, indicating that the generation of Fe/Mn spinel is energetically favorable than CeFe 2 O 4 in the system …”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from in situ XPS spectra agreed with the XRD patterns of the solid residues obtained from the magnetic separation after residue sulfation (Figure C), in which magnetite (FeFe 2 O 4 ) and jacobsite (MnFe 2 O 4 ) were indexed. Previous research also reported the shorter bond lengths of Fe–O (2.05 Å) and Mn–O (2.01 Å) in the octahedral sites of FeFe 2 O 4 and MnFe 2 O 4 , respectively, than Ce–O (2.18 Å) of CeFe 2 O 4 after the geometry optimization, indicating that the generation of Fe/Mn spinel is energetically favorable than CeFe 2 O 4 in the system …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the aluminosilicates in Al-rich CFAs may also host REYs. Another possibility is that, to some extent, Mn­(II) can also form hydroxides or oxides of ferromanganese with the EPR spectral feature of type (c) to adsorb or complex REYs. …”
Section: Resultsmentioning
confidence: 99%
“…These can create environmental risks if not managed properly. Overall, the recovery of REEs and other nuclear raw materials from waste is an important area of research due to the increasing demand for these elements and the potential environmental risks associated with their disposal (kursun et al 2018;Xiong et al 2019;Reynier et al 2021;Altıner et al 2021;zhou et al 2021;Guo et al 2022;Aziman et al 2023). These research investigations can also be evaluated in terms of sustainable development and feasibility.…”
Section: Introductionmentioning
confidence: 99%